CHARACTERISTICS OF TILAPIA PROTEIN HYDROLYSATE (Oreochromis niloticus) USING DIFFERENT CONCENTRATIONS OF PAPAIN ENZYME - Wisda Samosir P; Edison Edison; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTTilapia (Oreochromis niloticus) was one of the large freshwater fish commodities in Indonesia. The fish has the potential as a raw material for fish protein hydrolysates. Fish protein hydrolysates use specific and extensive ongoing enzymes capable of influencing the formation of peptides and amino acids. This study aimed to determine the effect of the addition of different concentrations of papain enzyme totilapia protein hydrolysates. This study used experimental methods with non factorial complete randomized design three replicates with different concentrations of papain enzyme treatment (5%;10%; and 15%). The parameters tested consisted of proximate analysis, degree of hydrolysis, large molecular weight protein and yield. The results showed that fresh tilapia had water content of 78.08% (wb); ash content of 18.06% (db); fat content of 4.37% (db); protein content of 74.22% (db) and carbohydrate content by difference of 3.33% (db). Tilapia protein hydrolysate with 15% concentration of papain enzyme was the best treatment with yield value of 10.03%; degree of hydrolysis of 3.35% and large molecular weight protein of 10.01%. Keywords: fish protein hydrolysate, papain enzyme, proximate, tilapia, yield